Review of Ongoing Activities and Challenges to Improve the Care of Patients With Type 2 Diabetes Across Africa and the Implications for the Future - Godman, Brian; Basu, Debashis; Pillay, Yogan; Mwita, Julius C.; Rwegerera, Godfrey Mutashambara; Anand Paramadhas, Bene D.; Tiroyakgosi, Celda; Okwen, Patrick Mbah; Niba, Loveline Lum; Nonvignon, Justice; Sefah, Israel; Oluka, Margaret; et al. (Frontiers in Pharmacology, 2020)
Background: There has been an appreciable increase in the number of people in Africa with metabolic syndrome and Type 2 diabetes (T2DM) in recent years as a result of a number of factors including lifestyle changes and urbanisation coupled with increasing levels of obesity. Currently there are 14.2 million adults in sub-Saharan Africa (SSA) with diabetes, mainly Type 2 diabetes (T2DM) (95%), estimated to grow to 34.2 million people by 2040. There are a number of issues to address to reduce the impact of T2DM including improving detection rates and access to services alongside addressing issues of adherence to prescribed medicines. There are also high rates of co-morbidities with infectious diseases such as HIV and TB in patients with T2DM in SSA that requires attention. Objective: Document ongoing activities across Africa to improve the care of patients with T2DM especially around issues of identification, access, and adherence to prescribed medicines. In addition, suggest potential ways forward to improve the care of patients with T2DM based on ongoing activities and experiences. Our Approach: Contextualise the findings from a wide range of publications including internet based publications of national approaches coupled with input from senior level government, academic and other professionals from across Africa to provide future guidance. Ongoing activities: A number of African countries are actively instigating programmes to improve the care of patients with T2DM starting with improved diagnosis. This recognises the growing burden of NCDs across Africa, which has been neglected in the past. Planned activities include programmes to improve detection rates and address key issues with diet and lifestyle changes, alongside improving monitoring of care and activities to improve adherence to prescribed medicines as well as address potential complexities involving diabetes patients with infectious disease co-morbidities. It is too early to fully assess the impact of such activities, Conclusion: There are a number of ongoing activities across Africa to improve the management of patients with diabetes including co-morbidities. However, more needs to be done considering the high and growing burden of T2DM in Africa. Ongoing research will help further benefit resource allocation and subsequent care.